DREAMING ABOUT THE FUTURE OF THE CHURCH IN AFRICA (Hekima Review, 2024)
Attempting to predict a possible, or even probable, profile of the future African Christian church from the present vantage point is something of a perilous task. Yet it should be seen neither as necessarily a naïve undertaking nor a futile exercise in futurology. On the contrary, the endeavor is quite rational and useful, particularly when guided by empirical data and other reliable indicators within the life of the church itself. Based on the environment in which the church lives, in which the pace of change can be overwhelming, to profile the future of the African church is an essential endeavor if the church is not to be overtaken by events. Even though, precisely because of the rapid transformations happening in the church and in the world, a completely accurate prognosis of the nature of the church to come may not be possible, it is still prudent to prepare for and plan for possible eventualities. A certain degree of “dreaming” about the future of the church is an unavoidable necessity.